Structure and function of proteins important in Mycobacterium tuberculosis energy metabolism - Mohamed Rehan, Aisyah (2009)
Mycobacterium tuberculosis (Mb) is the causative agent of tuberculosis (TB). A unique feature of Mtb is that it can remain dormant within the human host for years (persistance), and can survive in hypoxic and nutrient-depleted media. Coenzyme F420, a flavin analogue has been hypothesized to be associated with Mtb viability in anaerobic conditions and in persistence. This hydride carrier also acts as a redox sensor in Mtb by converting NO2 to NO released by Mtb-infected macrophages under aerobic condition. At least three genes are involved in the biosynthesis of F420; F420 biosynthesis A, B and C (fbiA, fbiB and fbiC). This PhD project will explore F420 biosynthesis using biophysical techniques. The fbiA and fbiB genes were cloned in a pET-Duet vector to test for protein interaction. While co-expression was unsuccessful, single expression of the genes produced soluble protein. FbiB has been purified and crystallized as small needles. Purification of a GST-tagged construct to eliminate proteolytic degradation and further fine screening is ongoing to obtain better quality crystals for X-ray diffraction. FbiC cloning into Gateway vectors is ongoing. Further biochemical and biophysical tests hopefully obtained in the near future will assist in our understanding of this unique coenzyme.